Processuridia, a new genus for two new species from China and Indochina (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Huang, Si-Yao; Volynkin, Anton V.; Zhu, Li-Juan; Xu, Yong-Qiang; Wang, Min; Fan, Xiao-Ling; Da, Wa (Zootaxa, 2022)
A new Nudariina genus, Processuridia S.-Y. Huang & Volynkin gen. n. is erected for two new species described herein: Processuridia thangka S.-Y. Huang & Volynkin sp. n. from southeastern Xizang, southwestern China and P. oreas Volynkin & S.-Y. Huang sp. n. from southeastern Yunnan, southwestern China and Mt. Fansipan, northern Vietnam, with P. thangka sp. n. as the type species of the genus. Based on molecular phylogenetic analysis, the new genus is found to be sister to the clade (Asuridia Hampson + Disasuridia Fang), but it can be easily distinguished from both genera by the unique wing pattern and genitalia features. Adults and genitalia of the aforementioned taxa are illustrated.